2010
DOI: 10.1016/j.plipres.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in host–pathogen interactions: Pathogens exploit the complexity of the host cell lipidome

Abstract: Lipids were long believed to have a structural role in biomembranes and a role in energy storage utilizing cellular lipid droplets and plasma lipoproteins. Research over the last decades has identified an additional role of lipids in cellular signaling, membrane microdomain organization and dynamics, and membrane trafficking. These properties make lipids an attractive target for pathogens to modulate host cell processes in order to allow their survival and replication. In this review we will summarize the ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 493 publications
(415 reference statements)
1
119
0
Order By: Relevance
“…It is well recognized that certain bacteria inhabiting a vacuole or phagosome, are able to synthesize some proteins and toxins to form holes in the vacuole membrane of their hosts to escape from these organelles (Van der Meer-Janssen et al, 2010). The disrupted cellular membranes could facilitate the entry of nanoparticles into the host cell and several reports have demonstrated that Gram-negative bacteria show an increased susceptibility to AgNPs (Sondi & Salopek-Sondi, 2004;Radzig et al, 2013), which makes these vehicles suitable candidates as an antimicrobial agent against NHP-B.…”
Section: _____________________mentioning
confidence: 99%
“…It is well recognized that certain bacteria inhabiting a vacuole or phagosome, are able to synthesize some proteins and toxins to form holes in the vacuole membrane of their hosts to escape from these organelles (Van der Meer-Janssen et al, 2010). The disrupted cellular membranes could facilitate the entry of nanoparticles into the host cell and several reports have demonstrated that Gram-negative bacteria show an increased susceptibility to AgNPs (Sondi & Salopek-Sondi, 2004;Radzig et al, 2013), which makes these vehicles suitable candidates as an antimicrobial agent against NHP-B.…”
Section: _____________________mentioning
confidence: 99%
“…Changes in membrane lipids alter the membrane identity of the organelle affecting trafficking. Recruiting or altering lipids is also important for metabolism, membrane dynamics and the tethering of effector proteins to the vacuole [23][24][25]. Several pathogens change the phosphoinositol signature found on their vacuoles.…”
Section: Role Of Lipids In Vacuole Stabilitymentioning
confidence: 99%
“…Bacterial SMases and PLases might contribute to the infection process in different hosts in several ways. Some of these enzymes hydrolyze structural membrane lipids and cause lysis of the host cells, contributing to bacterial colonization and/or dissemination and providing nutrients for pathogen survival and replication (14,15). Others generate bioactive lipids which activate endogenous mediators of cell death without inducing cellular lysis (15)(16)(17) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial SMases and PLases may act on vacuolar lipids, contributing to transform phagosomes into a replication-permissive niche or causing phagosomal membrane disruption that allows the pathogen to reach the host cell cytoplasm and survive by evading the host immune response ( Fig. 1) (14,15,18). Bacterial PLases from enteric pathogens degrade the phospholipid-rich mucus layer overlying the gastrointestinal mucosa, whereas those from lung pathogens cleave phospholipids from pulmonary surfactant, promoting nutrient release and contributing to tissue colonization, as well as in the case of surfactant cleavage to lung dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation